Reliable and authenticated data communication in wireless sensor networks. (11th September 2019) - Tripathy, Asis Kumar
In this paper, a reliable and authenticated data communication procedure for clustered wireless sensor networks (CWSN) is proposed. The scheme has several steps, like, assigning the identity, shared secret key and an encryption key to the sensor nodes by the base station (BS). Determined by the innovation propels in micro-electronics, it is conceivable to run some key management techniques at each sensor level. This step helps in authentication of the sensors and secured communication in the network. Hence the sensor nodes are deployed in the threatening environments, because of the self healing nature of the sensors, they will form a network to transmit the data. The secured communicating protocol described in this paper ensures that, when two sensor nodes are in correspondence, they must have experienced prior authentication and key pre-distribution process. This scheme is invariant to the environment where the clusters are formed dynamically and periodically.